ASSESSMENT OF UZBEKISTAN’S SOVEREIGN CREDIT RATING: AN ANALYSIS OF ECONOMIC REFORMS, GOLD AND FOREIGN EXCHANGE RESERVES, AND FISCAL RISK FACTORS - Poziljon Mansurjon o‘g‘li Mamadaliyev (International Journal of Business, Law and Political Science, 2026)
Objective: This study evaluates the factors underlying Uzbekistan’s sovereign credit rating improvement by examining the relationship between recent economic reforms, macroeconomic performance, gold and foreign exchange reserve accumulation, and fiscal risk indicators. The research aims to identify the principal drivers supporting the country’s upgrade to a “BB” sovereign rating while assessing the vulnerabilities that may constrain future rating improvements. Method: A mixed-method approach is employed, combining qualitative analysis of S&P Global Ratings’ sovereign assessment framework with descriptive analysis of key macro-financial indicators covering the period 2019–2025. The study examines trends in economic growth, external balances, public debt, fiscal performance, inflation, and international reserves, while also evaluating the influence of global gold price dynamics on Uzbekistan’s external liquidity position. Results: The findings indicate that sustained economic reforms, stronger institutional credibility, robust GDP growth, declining inflation, and the sharp increase in gold and foreign exchange reserves significantly strengthened Uzbekistan’s external resilience and contributed to the sovereign rating upgrade. However, persistent current account and fiscal deficits, rising public debt, and contingent liabilities associated with state-owned enterprises and public–private partnership projects continue to represent important structural risks. The analysis further shows that the recent surge in gold prices substantially enhanced reserve adequacy and external liquidity, reinforcing the country’s ability to withstand external shocks. Novelty: Long-term improvements in creditworthiness will depend not only on favorable commodity market conditions but also on the sustainability of structural reforms and macroeconomic policy credibility.